The Effect of Hemodialysis on Kinetic Segment of Left Ventricular in Stage V Chronic Kidney Diseases Patients - Systriana Esi Kamasita; Suryono Suryono; Yudha Nurdian; Yuli Hermansyah; Edy Junaidi; Mohamat Fatekurohman (Faculty of Nursing, Universitas Jember, 2018)
Chronic kidney disease (CKD) stage V attacks other organs such as heart that can cause cardiovascular disease (CVD). One of them is CVD caused by CKD stage V that is the kinetic segment of left ventricle. Cardiovascular disease occurs due to excess fluid and buildup of uremic toxin. Chronic kidney disease stage V can not be cured so it requires therapy that is hemodialysis (HD). Hemodialysis can reduce excess fluid, uremic toxin, and maintain electrolyte balance in stage V stage. Improved fluid and decreased uremic toxin can reduce the burden of the heart and strain so that blood supply to certain myocardial areas increases and the left ventricular kinetic segment increases. The purpose of this study is to determine the effect of HD on left ventricular kinetic changes in CKD stage V patients in dr. Soebandi hospital in Jember. The research design used was quasi-experimental one group pretest-postest design. The sample was 30 patients. Respondents were determined by nonprobability sampling technique with purposive sampling method. The data used are primary data and secondary data. Data analysis using Wilcoxon test. Based on the results of the study, the distribution of the sample based on the age of the most in the range of 45-54 years, based on the sex obtained more women, based on the duration of hemodialysis obtained the period of most hemodialysis> 24 months and based on blood pressure before and after hemodialysis obtained patients with hypertension. Hypothesis test using Wilcoxon test got p-value (0.000). From the results of the analysis can be concluded that there is influence of hemodialysis on kinetic segment of left ventricle in patient of CKD stage V in dr. Soebandi hospital in Jember.